PENGARUH SHOPPING LIFESTYLE, SALES PROMOTION DAN E-SERVICE QUALITY TERHADAP KEPUTUSAN PEMBELIAN PENGGUNA TOKOPEDIA DI DESA JOTANGAN MOJOKERTO - Fitra Dwi Prayogo; Christina Menuk Srihandayani; Tony Susilo Wibowo (Majalah Ekonomi, 2021)
Advances in technology and the flow of information have caused some people to be increasingly able to open themselves to developments in global technology, especially the internet. The condition indirectly brings the phenomenon of changing lifestyles in society, namely by using the internet as a means for digital shopping or what we usually know as e-commerce. The aim of this study is to understand the influence of shopping lifestyle, sales promotion and e-service quality on purchasing decisions of Tokopedia users. The quantitative approach was used in this research with a sample of 100 respondents who were taken through the accidental sampling technique. Then the data were collected using a questionnaire that was arranged coherently and had met the validity and reliability requirements. Multiple linear regression is used in analyzing data that have previously passed the classical assumption test and meet the necessity. The partial test results show that shopping lifestyle, sales promotion, and e-service quality have a significant influence on the purchasing decisions of Tokopedia users and the test results simultaneously show that shopping lifestyle, sales promotion, and e-service quality have a significant effect on Tokopedia users' purchase decisions.